2021
DOI: 10.1016/j.jcrc.2020.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Early neuromuscular electrical stimulation reduces the loss of muscle mass in critically ill patients – A within subject randomized controlled trial

Abstract: Please cite this article as: J. Segers, I. Vanhorebeek, D. Langer, et al., Early neuromuscular electrical stimulation reduces the loss of muscle mass in critically ill patients -A within subject randomized controlled trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
(73 reference statements)
0
16
0
1
Order By: Relevance
“…There were 12 (14.5%) studies utilised non-randomised or case-matched controls, with eight were on patients [ 56 , 80 , 83 , 88 , 94 , 111 , 112 , 115 ]. There were 40 (48.2%) studies used a single group, self-controlled design, with nine investigated on patients [ 55 , 58 , 59 , 63 , 85 , 98 , 106 , 117 , 120 ]; while there was one (1.2%) single case study on a patient [ 82 ]. Sixteen (16, 19.3%) studies were conducted in clinical settings and 67 (80.7%) were in laboratory settings ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 12 (14.5%) studies utilised non-randomised or case-matched controls, with eight were on patients [ 56 , 80 , 83 , 88 , 94 , 111 , 112 , 115 ]. There were 40 (48.2%) studies used a single group, self-controlled design, with nine investigated on patients [ 55 , 58 , 59 , 63 , 85 , 98 , 106 , 117 , 120 ]; while there was one (1.2%) single case study on a patient [ 82 ]. Sixteen (16, 19.3%) studies were conducted in clinical settings and 67 (80.7%) were in laboratory settings ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were 40 articles (48.2%) that reported the effects of chronic peripheral stimulation (training), with 31, six and three applying ES, VB or ND, respectively; and 43 (51.8%) that investigated the acute effects, with 22, 12 and nine applying ES, VB or ND, respectively. Among the 40 studies that used chronic stimulation, the typical protocols involved 2–5 sessions per week (except for one ES study [ 80 ] that applied 10 sessions per week, and three ES studies [ 51 , 92 , 98 ] and one VB study [ 111 ] that trained for seven sessions per week), for 1–12 weeks with a total of 9–36 training sessions (with exception of one ES study [ 55 ] that lasted 56 weeks and involved 280 sessions) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Um fato interessante foi que a melhora foi observada principalmente em pacientes mais graves e mais fracos 10 . Então, a melhor recuperação pode ser influenciada pelo estado clínico dos pacientes em que aqueles mais gravemente enfermos perdem mais massa muscular e podem se beneficiar mais da intervenção 24 . No entanto, a EENM não influenciou a espessura da camada muscular, mas foi associada a uma maior recuperação da força muscular durante a permanência na UTI 12 .…”
Section: Estimulação Elétrica Neuromuscular (Eenm)unclassified
“…Neuromuscular electric stimulation (NES) increased muscle mass and improved the Timed Up and Go test (TUG) (31). NEMS reduced muscle mass loss in critically ill patients (32). A meta-analysis found that vibration therapy in older persons improved strength, five times sit to stand and TUG (33).…”
mentioning
confidence: 99%